The Analysis of Croissants, Lovely Bread from Lovely Heart Students at Politeknik Pariwisata Bali - Yuna Sugiantari, Ni Made; Pramesti Putri, Ni Luh Putu Dela; Amara Laksmi, Ni Made Dinda; Antari Putri, Ni Made Sherly; Sintya Dewi, Ni Putu Ayu Gita; Surya Advika, I Putu Dipta Surya; Santi Diwyarthi, Ni Desak Made (Jurnal Multidisiplin West Science, 2024)
This research aims to study the experience of making croissant pastries. It is a qualitative study with a phenomenological approach. Qualitative research methods are geared towards gaining a profound understanding of phenomena from the viewpoint of the subjects involved. These methods, such as depth interviews, participant observation, and literature review, are commonly used. Depth interviews delve into comprehensive discussions with respondents to grasp their perspectives thoroughly, while participant observation involves direct engagement to comprehend the dynamics of a situation. Meanwhile, literature review examines pertinent sources to grasp the existing knowledge regarding croissants, alongside the obstacles and prospects for their advancement. In summary, croissants are cherished for their delectable taste, adaptability, and appeal to younger consumers. Their adherence to traditional production techniques, French heritage, and strict quality control measures underscore their authenticity and widespread adoration. With their capacity to cater to varied preferences and visually striking appearance, croissants remain a beloved pastry enjoyed and crafted by many.